Pengaruh Kualitas Pelaporan Keuangan Berbasis Akuntansi dan Berbasis Pasar terhadap Kesenjangan Informasi pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia - Wahyuliza, Suci (JUSIE (Jurnal Sosial dan Ilmu Ekonomi), 2018)
This research aims to test the influence of the quality of financial reporting accounting based and market based on the asimetri of information. The sample used the manufacturing companies listed on the Indonesia stock exchange from 2007 untill 2011. Using a Purposive sampling technique of Sampling and retrieved samples of as many as 41 companies.Hypothesis test results showed that the quality of financial reporting based accounting is represented with three indicator are persistence and predictability has no effect on the asimetri of information whereas the effect on income smoothing indicator asimetri of information. Further market based financial reporting quality is represented by three indicators, namely the relevance of the value and timeliness of the Asimetri information has no effect while the indicator of conservatism has influence on the asimetri of information.